Validity of the Nintendo Wii® balance board for the assessment of standing balance in Parkinson's disease. (April 2013) - Holmes, Jeffrey D; Jenkins, Mary E; Johnson, Andrew M; Hunt, Michael A; Clark, Ross A
Background: Impaired postural stability places individuals with Parkinson's at an increased risk for falls. Given the high incidence of fall-related injuries within this population, ongoing assessment of postural stability is important. Objective: To evaluate the validity of the Nintendo Wii ® balance board as a measurement tool for the assessment of postural stability in individuals with Parkinson's. Subjects: Twenty individuals with Parkinson's participated. Intervention: Subjects completed testing on two balance tasks with eyes open and closed on a Wii ® balance board and biomechanical force platform. Main Measures: Bland–Altman plots and a two-way, random-effects, single measure intraclass correlation coefficient model were used to assess concurrent validity of centre-of-pressure data. Results: Concurrent validity was demonstrated to be excellent across balance tasks (intraclass correlation coefficients = 0.96, 0.98, 0.92, 0.94). Conclusions: This study suggests that the Wii ® balance board is a valid tool for the quantification of postural stability among individuals with Parkinson's.